Tuvinian Fairytales Based on the Mongol Story Plots: “Magic Dead Man” Collection of Short Stories - Dongak, Antonina Saar-oolovna (Journal of History Culture and Art Research, 2018)
In the course of historical development, cultural contacts of the Tuvinian people with the Mongol-speaking peoples were very diverse and intensive. Tuvinian-Mongol folklore literature contacts, which are one aspect of close cultural interactions of the peoples of Central Asia and Sayan-Altai regions, are of a great interest for researchers. One of the most prominent phenomena in the Tuvinian-Mongol folklore interrelations is a wide range of Central Asian versions of the Geser, Dzhangar, Khan-Kharanguy and other series of epic tales, along with various collections of Old Mongolian literature stories, which added a new plot and creative stylistic content and new genre form, the framed fairy tale, to the Tuvinian folklore. Thus, in Tuvinian folklore, there were common plots adopted from the Mongolian literature in the framed novelette genre – Arzhi-Bordzhi, The Magic Dead Man, The Tales of a Parrot as well as Bigarmidzhid and Panchatantra, which, due to an active dispersion of Buddhism at the end of the 18th – the beginning of the 19th century began to spread in Tuva and Tuvinian folklore in fairytale form together with the religious literature. The theoretical and methodological basis of the given research is structured around the works of leading experts in oriental, literature and folklore studies. A great contribution into the study of intercultural literary connections and folklore literature interconnections of the oriental people was made by E.M. Meletinsky, I.D. Serebryakov, P.A. Grintser, S.U. Nekludov, A.D. Tsendina, E.N. Afanasyeva and other researchers in the works and articles. The aim of this research is to define the role and importance of Mongolian literary monument “Magic Dead Man” (Mong.: Shiditu hūr) in the expansion of Tuvinian folklore repertoire and enriching its plot and motif components as well as the introduction of a new genre form in the Tuvinian folklore – the framed fairytale, which comes from the genre of a framed novelette, which was created within the Ancient Indian literary tradition. The study was held on the complex approach level with the implementation of the comparative-typological and comparative-textological methods, which allowed completing a systematic analysis of the literary and folklore poetic and stylistic models. The Tuvianian storytelling tradition, based on the ancient epic one, appeared to be accessible for perceiving the international elements and a prosperous foundation, which created fresh aspects in the form of new fairytale plots. The analyzed fairytales prove that the Tuvinian people not only mechanically adopted these plots, but were also able to creatively transform them in their creative writing.